Health status of persons with dementia and caregivers’ burden during the second wave of COVID-19 pandemic: an Indian study - Mukherjee,Ruchira (2022)
ABSTRACT. Due to the disruption of normal flow of treatment during the restrictions related to the coronavirus disease 2019 (COVID-19) pandemic, the health status of persons with dementia (PwD) and their caregivers’ burden might worsen. Objective: The article aims to find out the health status of PwD and caregivers’ burden during the peak of second wave of COVID-19 and make a comparison with the preceding trough phase. Methods: The study was conducted with 53 PwD and their caregivers in two phases. On their visit to the hospital during the unlock phase (phase 1), data were collected for CDR from PwD, and NPI-Q and ZBI from their caregivers. During the peak of second wave (phase 2), data were collected for NPI-Q, ZBI, and DASS-21 through telephonic communication, and statistical analyses were performed on the collected data. Results: Significantly higher caregiver burden (p=0.001) and neuropsychiatric symptoms (NPSs) [both in severity (p=0.019) and distress (p=0.013)] were observed among the respondents during the peak of second wave of the pandemic as compared to the preceding trough phase. Positive correlations were observed between the caregiver burden and depression, anxiety, and stress of the caregivers (p<0.001) and between the severity of dementia in PwD and caregiver burden (p<0.001) for both the first and second phases. Positive correlation was also observed between the severity of dementia in PwD and depression (p=0.042) and stress (p=0.023) of caregivers. Conclusions: Significant increase in the burden and distress was observed among caregivers due to increased NPSs of PwD during the second wave of COVID-19 pandemic.